The Role of Family Eating and Activity Habits in the Relationship Between Parenting and Feeding Practices on Child Eating Behavior - Nadirawati Nadirawati; Chatarina Suryaningsih; Felina C. Young; Hartiah Haroen; Susilowati Susilowati (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Nutritional problems in children, including underweight and stunting, remain a global health challenge, particularly in Indonesia. This study examines the influence of parenting styles and feeding practices on children's eating behavior, with family eating and activity habits as a mediating variable Methods: A cross-sectional survey design was employed in this study, involving 225 mothers of stunted and underweight children aged 2–5 years in Cimahi City, Indonesia. The study investigated key variables including parenting styles, feeding practices, family eating and activity habits, and children’s eating behavior. Data were gathered using validated questionnaires and analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach. This analytical technique enabled the examination of complex causal relationships and latent constructs, including mediation pathways. The research complied with ethical standards and received approval from the Health Research Ethics Committee of the Faculty of Health Science and Technology, Jenderal Achmad Yani University, Cimahi, on May 31, 2024 (Certificate No. 086/KEPK/FITKes-Unjani/2024). Results: The results showed that parenting styles (? = 0.222, t = 3.630, p < 0.001) and feeding practices (? = 0.243, t = 3.640, p < 0.001) significantly influenced children's eating behavior. Family eating and activity habits significantly mediated the relationship (? = 0.448, t = 6.401, p < 0.001). Feeding practices and parenting styles also predicted family habits (f² = 0.369 and 0.462, respectively). Conclusion: These findings highlight the importance of family eating habits in shaping children's eating behavior and addressing malnutrition and stunting. Thus, family-based interventions are needed to improve healthy feeding practices and promote positive eating behavior in children at risk of malnutrition in Indonesia, aiming to achieve zero stunting and malnutrition.